A supramolecular system that strictly follows the binding mechanism of conformational selection - Liu-Pan Yang (Nature Portfolio, 2020)
Conformational selection is one of the two dominant binding mechanisms in biology, but has rarely been studied in synthetic systems. Here, the authors report a supramolecular system that strictly follows the binding mechanism of conformational selection.